Probing late-time annihilations of oscillating asymmetric dark matter via rotation curves of galaxies - Júlia G. Mamprim; Guillermo Gambini; Luan B. Arbeletche; Marcos Olegario; Vitor de Souza (European Physical Journal C: Particles and Fields)
Abstract In this paper, we explore the Oscillating Asymmetric Dark Matter (OADM) model to address the core-cusp problem, aiming to resolve the discrepancy between the predictions of the $$Λ CDM$$ Λ CDM cosmological model and the observed dark matter profiles in dwarf spheroidal galaxies. The reactivation of dark matter annihilation during the structure formation epoch is possible if there is a small Majorana mass term that breaks the conservation of dark matter particle number, leading to oscillations between dark matter and its antiparticle. We analyzed the effects of the annihilation mechanism in the galaxy rotation curves of the SPARC and LITTLE THINGS catalogs. We searched for the characteristics of the OADM model which best describes the data. Our results show that the OADM model can successfully turn originally cusp-type halos into core-type ones according to our data sample.